Halal consumerism in the fast-food industry: investigating awareness, literacy, and religious moderations on youth purchasing behavior - Nadia Musfika; Engriani, Yunita (Marketing Management Studies, 2024)
This study aims to analyze the influence of halal awareness and halal literacy on the purchase intention of packaged fast-food products among young Muslim consumers in Padang city, with religiosity as a moderating variable. The population comprises young Muslims in Padang city who consume fast food, with a sample size of 150 respondents. Data were collected through questionnaires and analyzed using SmartPLS software. The results indicate that: (1) Halal awareness has a positive and significant influence on the purchase intention of fast food among young urban Muslims in Padang city; (2) Halal literacy has a positive but insignificant influence on the purchase intention of fast food among young urban Muslims in Padang city; (3) Religiosity moderates the influence of halal awareness on the purchase intention of fast food among young urban Muslims in Padang city; and (4) Religiosity does not moderate the influence of halal literacy on the purchase intention of fast food among young urban Muslims in Padang city.